Depan Volume 8, Nomor 1, Januari 2019 - Volume 8, Nomor 1, Januari 2019, Volume 8, Nomor 1, Januari 2019 (Teknik Desain Mekanika; Vol 8 No 1 (2019): Januari 2019 : Teknik Desain Mekanika, 2019)
Depan Volume 8, Nomor 1, Januari 2019